Kajian identiti korporat syarikat rakaman Borneo Headhunters Music Production (BHMP) - Suif, Z. (Universiti Malaysia Sarawak, UNIMAS, 2007)
Sarawak music industries is currently monopolize with the concept of joget. However, the Borneo Headhunters Music Production is the only Sarawak Recording Company that product album with pop-rock commercial music. This research concludes identifying the problem with the company coporate identity and to find a suitable type of promotion strategy that can be use to compete with other music production in Sarawak.